Synchronizing estrus in heifers with prostaglandin and Syncro-mate B - Heersche, G. Jr.; Kiracofe, G.; McKee, M.; Davis, Duane L.; Brower, G.R. (Kansas State University. Agricultural Experiment Station, 2011)
Forty-seven of 50 heifers were in estrus 1 to 5 days after an injection of prostaglandin given when an ear implant of Synchro-mate B was removed. The implant had been in place one week. Thirty of the 47 (63.8%) heifers with synchronized estrus conceived on first artificial insemination. Twenty untreated heifers were in estrus in 27 days; 13 (65%) conceived on first artificial insemination.
Keywords: Beef; Estrus; Prostaglandin; Syncro-mate B